Best references for the QPA of Portland cement. Issue 2 (June 2022) - Fawcett, T. G.; Blanton, J. R.; Kabekkodu, S. N.; Blanton, T. N.; Lyza, J.; Broton, D.
Abstract : Cement references were reviewed and whole pattern methods were developed for the quantitative phase analysis (QPA) of Type I Portland Cements. A set of control references were established for phase identification and quantitative analysis using laboratory diffractometers. Both RIR and Rietveld whole pattern fitting methods were used in the analyses. A block refined, parameter restricted, Rietveld method produced the best QPA results by comparison with known mixtures. Similar to prior literature findings, care has to be taken because of the severe peak overlap of the major calcium silicate and calcium aluminate phases in Portland cement and the complexity of the chemistry and structures involved. Two of the four major phases identified are doped supercells and the major C3S phase is also disordered.